Effectiveness of educational-supportive intervention in satisfaction of Iranian family members of intensive care unit patients - Ali Navidian; Jahangir Rezaei; Hossainali Payan (Gonabad University of Medical Sciences, 2018)
Education and support based on family's needs may reduce anxiety and increase satisfaction of family members of hospitalized patients in Intensive Care Unit (ICU). This study was conducted to determine the effect of educational-supportive intervention on satisfaction of family members. In this quasi-experimental study, 154 participants of family members of hospitalized patients in ICU in Zahedan (Iran) were studied. The participants were allocated to intervention and control groups. Family Satisfaction-ICU (FS-ICU) was used as data collection tool. The validity and reliability of questionnaire was confirmed in Iran. The questionnaires were completed by both groups before and after one- week intervention. The mean change in the score of satisfaction with performance, comfort and participation in decision-making of family members of patients after educational-supportive intervention were 76.62±14.34, 73.86±4.15, and 31.61±19.323 respectively in the intervention group. These scores were significantly higher than those of control group (43.5±3.62, 22.63±5.83 and 18.12±13.84). Analysis of covariance through control of covariate showed that the mean score of satisfaction of family members concerning the three sub-scales were significantly different in two groups after intervention. According to the effect of educational-supportive intervention on the increase of family satisfaction, it is essential to apply these interventions in educational programs and family-centered care. This action reduces the family's concern as well as increases their motivation and power in caring after patient's discharge.